Preclinical safety and efficacy evaluation of 'BioCaS' bioactive calcium sulfate bone cement. (3rd February 2017) - Sandhya, Sony; Mohanan, Parayanthala Valappil; Sabareeswaran, Arumugan; Varma, Hari Krishna; Komath, Manoj
Abstract: A new bioactive calcium sulfate-based formulation (named 'BioCaS') has been developed for bone filler applications. This is a self-setting injectable cement where the preset form comprises bassanite obtained from the uniform submicron-sized precursor crystals of gypsum, modified with hydrogen orthophosphate ions. The results of the safety and efficacy evaluation of BioCaS cement, done as per the International Standards and guidelines, are presented in this paper. The study plan consisted of in vitro screening tests of cytotoxicity and haemolysis and in vivo biocompatibility evaluation, including an acute systemic toxicity test (in mice), an intracutaneous reactivity test (in rabbits), a pyrogen test (in rabbits) and a maximization sensitization test (in guinea pigs). The efficacy of the material in healing bone defects was investigated by implanting it in artificially created defects in rabbit femora, with clinically established hydroxyapatite porous ceramic as the control, followed by histological analysis at 12, 26 and 52 weeks. Set BioCaS cement consisted of hydrogen orthophosphate incorporating low-dimensional gypsum crystal lattices, the bioactivity of which has been identified by immersion in simulated body fluid. BioCaS was proved to be non-cytotoxic and non-haemolytic in the screening tests. In the live/dead assay, human osteoblast-like human osteosarcoma cells adhered well and spread on the surface of the material, attaining typical morphology and affirming the bone cell compatibility of the material. In the biocompatibility evaluation there were no acute systemic effects and the material proved non-pyrogenic. There was no intracutaneous erythemic or oedematous reactivity and no hypersensitivity observed in the Magnusson–Kligman method. The material satisfied the biocompatibility requirements. Bone implantation study revealed BioCaS to be osteoconductive and its efficacy of healing the experimental bone defects in rabbit femora is on a par with that of hydroxyapatite ceramic. The material resorbed at a pace matching that of new bone formation. This property of osteotransductivity will help the defect to heal and gain strength faster.